Reverse Zoonoses: Change of the Route of Zoonotic Diseases Transmission between Humans and Animals - Samadi, Assadullah (Journal of Natural Sciences – Kabul University, 2022)
Most scientific research often focuses on zoonotic diseases where animals are the primary source of infection. However, recent studies highlight the role of humans in maintaining and transmitting zoonotic disease agents to animals. Such zoonoses are termed reverse zoonoses (zooanthroponoses). The transmission of zoonotic agents from humans to livestock, companion animals, and wildlife has been confirmed, with SARS-CoV-2, influenza viruses, Mycobacterium spp., and methicillin-resistant Staphylococcus aureus (MRSA) being particularly significant threats to human and animal health. Furthermore, animals infected through this route can serve as reservoirs, transmitting these pathogens to humans and other susceptible animals.